The Impact of Tourism in Tanzania on Community Development: Theoretical Perspectives - Mitekaro, Musa Gideon (Advances in Social Sciences Research Journal, 2016)
The paper aimed to present atheoretical review of The Impact of Tourism in Tanzania on Community Development with a specific debate on how tourism may relate positively or negatively to socio-economic development. The pro-poor theory, social justice theory and collective action tourism theory were reviewed so as to relate them to the study of Arusha Region.The study used a theoretical review approach in which Community Based Tourism theory (CBT) was highlighted within its contribution towards participation together with other relevant theoretical perspectives. From the literature and related studies, it was evident that the government of Tanzania through the Ministry of Tourism and Natural Resources has policies which do not adequately mainstream local community participation; various studies across the world and sub-Saharan Africa have shown weak relationship between tourism and community development. Since Tanzania as a country is not exempt is recommended to study this phenomenon empirically in order to enhance the relationship.